Effect of chemical steeping on yields of glucose and xylose from dilute acid hydrolysis of extract from oil palm trunk - Wong, Lih Jiun; H’ng, Paik San; Chuah, Luqman Abdullah; Mohamad Tahir, Paridah; Chin, Kit Ling (College of Natural Resources, North Carolina State University, 2021)
The effectiveness of chemical steeping was examined as a novel pretreatment prior to hydrolysis to influence the extractable yield of glucose and xylose from oil palm trunk (OPT). The chemical steeping parameters were 0.2% sodium metabisulphite (w/v), 0.5% lactic acid (v/v), 26 ± 2 °C, and 1 h, followed by dilute acid hydrolysis (2%, 4%, and 6% of sulphuric acid (v/v); 115 °C, 120 °C, and 130 °C; 15 min, 30 min, and 60 min). For comparison, the glucose and xylose yield extracted from untreated OPT was also examined. Thermal analysis showed that the lactic acid and sodium metabisulphite successfully degraded the lignocellulose of OPT. The total extracted glucose and xylose yield was improved, and was approximately 2.5% to 28.8% higher than the yield extracted from non-pretreated OPT fines. RSM analysis showed that the 130 °C x 50 min x 2% was predicted as the optimum parameters for the extraction of glucose and xylose through chemically treated OPT, and followed the dilute acid hydrolysis process. Analysis of variance showed that the hydrolysis parameters were significant model terms for the glucose and xylose yield. In conclusion, chemical steeping was successful as a pretreatment to increase the extractable glucose and xylose yield from OPT.